2019
DOI: 10.1007/s40843-019-1183-0
|View full text |Cite|
|
Sign up to set email alerts
|

A novel GSH responsive poly(alpha-lipoic acid) nanocarrier bonding with the honokiol-DMXAA conjugate for combination therapy

Abstract: The key to improve the therapeutic efficacy for cancer treatment is to increase the delivery of drugs to tumors. For this purpose, tumor-microenvironment stimuliresponsive materials have great potential. Here, we prepared a new nanomedicine by bonding the conjugate of honokiol (HNK) and 5,6-dimethylxanthenone-4-acetic acid (DMXAA) to a glutathione (GSH)-responsive nanocarrier, poly(α-lipoic acid) polyethylene glycol. The nanomedicine would disintegrate due to the high level of GSH at the tumor sites, achieving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Owing to the formation of ester bonds between HCPT and GA, the chemical shift of peaks f, g, h, and i in HCPT moved to a lower field (peak j, k, m, and n of HCPT-GA), and the formation of new peaks c, d, and e in HCPT-GA also showed the successful synthesis of HCPT-GA. Meanwhile, 13 C NMR quantitative spectrum (Figure 2c) showed that the integration ratio of peak u, v, or x to peak w or y is 1∶1, which also proved that HCPT-GA had indeed been obtained and the residual anhydride had been removed thoroughly. Subsequently, HCPT-Gu was characterized by 1 H NMR in DMSO-d6 and ESI-MS (ESI+).…”
Section: Synthesis Of Hcpt-gumentioning
confidence: 72%
See 2 more Smart Citations
“…Owing to the formation of ester bonds between HCPT and GA, the chemical shift of peaks f, g, h, and i in HCPT moved to a lower field (peak j, k, m, and n of HCPT-GA), and the formation of new peaks c, d, and e in HCPT-GA also showed the successful synthesis of HCPT-GA. Meanwhile, 13 C NMR quantitative spectrum (Figure 2c) showed that the integration ratio of peak u, v, or x to peak w or y is 1∶1, which also proved that HCPT-GA had indeed been obtained and the residual anhydride had been removed thoroughly. Subsequently, HCPT-Gu was characterized by 1 H NMR in DMSO-d6 and ESI-MS (ESI+).…”
Section: Synthesis Of Hcpt-gumentioning
confidence: 72%
“…HCPT-GA was characterized by 1 H NMR and 13 C NMR in DMSO-d6. As shown in Figure 2b, a new carboxyl peak p of HCPT-GA appeared, while the hydroxyl peak j of HCPT disappeared.…”
Section: Synthesis Of Hcpt-gumentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of local chemotherapy combined with thrombosis achieved excellent tumor suppression in mouse. Furthermore, the GSH‐responsive nanoparticle combined with DMXAA had also been reported (Z. Liu et al, 2020). In another study, a CDDP‐loaded nanoparticle targeted by coagulation factors was used in combination with DMXAA (Song, Tang, Zhang, Li, et al, 2016; Song, Tang, Zhang, Wen, et al, 2016).…”
Section: Engineered Nanomedicines For Vascular Infarction Strategymentioning
confidence: 94%
“…The antitumor effect of SDT is highly dependent on the reactive oxygen species (ROS) caused by acoustic sensitizers and low-intensity ultrasound (US). During the SDT process, tumor cells typically produce high levels of endogenous antioxidant anti-glutathione (GSH) [5][6][7][8][9], attenuating the intracellular ROS level and hindering the efficiency of SDT. To address this issue, researchers often use nanomaterials, such as MnWO X [10], MnO 2 [11,12], and Au [13] to achieve GSH depletion [7,14].…”
Section: Introductionmentioning
confidence: 99%